STUDY OF THE STRATIFICATION PROCESS AT THE RESERVOIR OF THE HYDROELECTRIC POWER PLANT GOV. PEDRO VIRIATO PARIGOT DE SOUZA (CAPIVARI-CACHOEIRA), PARANÁ, BRAZIL. - Lopes, Sarah Meier; de Arruda, Nicole Machuca Brassac; Pagioro, Thomaz Aurélio (Eclética Química, 2018)
The study of the stratification processes in reservoirs is important because they happen along with several physical and chemical changes in the water, as in the distribution of dissolved gases and nutrients. The aim of this work was to study the stratification process of the Capivari-Waterfall Hydroelectric Power Plant, based on the data of the vertical profiles of dissolved oxygen and temperature, as well as the comparison of them with the calculation of Froude’s Densimetric Number, and reservoir residence time. The data used are part of the self-monitoring program carried out by COPEL. These data were collected quarterly between 2005 and 2016. The hydraulic and operational data from the reservoir were used to calculations. According to the measurements of dissolved oxygen and temperature, it was considered to be stratified during almost all the year, with a trend of circulation in the colder months, this behavior characterizes lakes with warm monomictic circulation pattern. Therefore, the result of Froude’s Densimetric Number, corresponded correctly with the observed. Regarding the residence time, this was not consistent with the results obtained, from the models. The use of different methodologies in evaluating circulation in reservoirs should be used in order to make the best management decision.